Plugged in. (American City & County, 2009)
The article reports on several computer software acquisitions by U.S. counties and government agencies. The Central Dispatch of Montcalm County, Michigan has purchased computer-aided dispatch, records management and mobile computing software from Sungard Public Sector while Cody Systems has supplied the records management software of the Washington Department of Fish and Wildlife. The city of Buffalo, New York has also purchased reporting and web-based software from Infor PublicSector.